Community Perspective: Assessment of Knowledge, Attitudes and Information Exposure to Participation in the Covid-19 Vaccination Program - Istiana; Diauddin; Anhar, Vina Yulia; Alfanie, Iwan; Bakhriansyah, Mohammad; Rahman, Fauzie; Jayadi, Yusef Dwi; Fatimah, Husnul (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2022)
Vaccine's acceptance is affected by several factors such as their knowledge and perception of the possible spread of Covid-19, perception of vaccine safety, logistics, perception of vaccine efficacy and perceived risk, etc. A source of knowledge that has the potential to influence public acceptance or rejection of the Covid-19 vaccine, it is critical to disseminate clear and reliable information about vaccine safety and efficacy to gain public trust. This study aims to analyze the relationship between knowledge, attitudes and information exposure with community participation in the Covid-19 vaccination program. Quantitative research using analytical descriptive with cross-sectional approach. The research was carried out in the province of South Kalimantan. The sampling technique used accidental sampling with a total sample of 252 respondents. Data collection is done online using a questionnaire instrument via Google Form. Fisher exact test was used as statistical test with CI: 95% (α: 0.05). There is a relationship between knowledge and participation in the vaccination program (p-value: 0.023 < 0.05). There is no relationship between attitude (p-value: 0.168 > 0.05) and information exposure (p-value: 0.280 > 0.05) with participation in the vaccination program. The availability of transparent information on vaccine efficiency and safety can play a key role for everyone to be encouraged to vaccinate without hesitation.